An In Vitro Model of Murine Osteoclast-Mediated Bone Resorption - Xiaoyue Sun; Zijun Wang; Yi Tang; Stephen Weiss; Lingxin Zhu (Bio-Protocol)
Osteoclasts are terminally differentiated multinucleated giant cells that mediate bone resorption and regulate skeletal homeostasis under physiological and pathological states. Excessive osteoclast activity will give rise to enhanced bone resorption, being responsible for a wide range of metabolic skeletal diseases, ranging from osteoporosis and rheumatoid arthritis to tumor-induced osteolysis. Therefore, the construction of in vitro models of osteoclast-mediated bone resorption is helpful to better understand the functional status of osteoclasts under (patho)physiological conditions. Notably, it is essential to provide an in vivo–relevant bone substrate that induces osteoclasts to generate authentic resorption lacunae and excavate bone. Here, we summarize the experimental design of a reproducible and cost-effective method, which is suitable for evaluating the regulatory mechanisms and influence of molecular agonists and antagonists as well as therapeutics on osteoclast-mediated bone-resorbing activity.